Plasma progesterone concentrations in Toggenburg goats submitted to estrous synchronization reusing autoclaved intravaginal progesterone devices. - BRANDÃO, F. Z. (2011)
Abstract: The aim of this study was to evaluate plasma P4 concentration in Toggenburg goats receiving autoclaved progesterone devices for estrous synchronization. Progesterone analysis allows us to infer that the autoclaving process does not influence progesterone availability and so this technique can be a simple and valuable tool to reduce sanitary risks of disease transmission without alterating fertility in goats. [Concentrações de progesterona plasmática em cabras da raça Toggenburg submetidas à sincronização de estro reutilizando dispositivos intravaginais de progesterona autoclavados].